Studi Kajian Realisasi Pembiayaan Pemerintah Daerah Kabupaten Deli Serdang - Pitri Br. Sitorus; Yusnita Yusnita; M. Aga Ashari; Rusiadi Rusiadi; Dewi Mahrani Rangkuty (Student Research Journal, 2023)
This review study aims to analyze the realization of local government financing of Deli Serdang Regency. This study is a descriptive qualitative literature method through literature study, with the data used secondary data obtained from the Deli Serdang Central Bureau of Statistics. The study results explain that the government financing expenditure of Deli Serdang Regency from 2016 to 2022 has changed due to the different growth rates each year, seen from how much regional payment and regional financing are needed in that year. The development of government expenditure is the impact of national income growth. At the same time, federal income growth affects economic development, where economic development increases the population and public facilities also grow. And government spending affects the unemployment rate, where an increase in government spending reduces the unemployment rate in the region.